Pengaruh Pembelajaran Jarak Jauh Masa Pandemi Covid-19 terhadap Kemampuan Baca Al-Qur’an Siswa pada Mata Pelajaran PAI di SDIT Khoiru Ummah - Ahmad Sururi; Oking Setia Priyatna; Retno Triwoelandari (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
The Covid 19 pandemic in 2021 caused a major impact on the world of education, in the implementation of learning activities the government provided rules for implementing distance learning activities (PJJ). Therefore, PAI teachers must strive to provide appropriate learning so that students can continue to improve their reading skills of the Qur'an. The purpose of this study was to determine the effect of the implementation of Distance Learning (PJJ) on students' reading ability of the Qur'an. The method in this study uses a quantitative descriptive research approach. The findings of this study are that an average value of 81.2368 was obtained before the implementation of the PJJ, and the value after the implementation of the PJJ obtained an average value of 82.0263, which means that there is an increase in the average value during the pandemic but it is not significant. Then the results of the T test calculation obtained a significance value of 0.110 > 0.05, so it can be concluded that there is no significant effect between the effect of distance learning during the covid-19 pandemic on students' reading ability of the Qur'an at SDIT Khoiru Ummah. Keywords: Distance Learning (PJJ); Ability to read the Qur'an